Key issues in development (Palgrave Macmillan, 2004)
The notion of development has evolved from a relatively straightforward concern with industrialization plus increasing gross domestic product to a much more complex mix of quality of life, participation, empowerment and good governance - all of which have remained elusive to many of the world's poor. This major new text provides a critical interdisciplinary introduction to the theory, practice and study of development at the start of the twenty-first century.